TEKNIK SELF-CONTROL DALAM KONSELING KELOMPOK UNTUK MENURUNKAN PROKRASTINASI AKADEMIK SISWA YANG KECANDUAN GAME ONLINE - Fergi Syuhada; Fakhri Yacob (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of self-control techniques in group counseling to reduce academic procrastination among students addicted to online games at SMAN 1 Banda Aceh. The research used a quantitative approach with a pre-experimental method through a One Group Pretest-Posttest Design. The population consisted of 103 students, while the sample was 8 students selected using purposive sampling based on specific criteria, namely students who actively played online games and experienced academic procrastination. Data collection was conducted using an academic procrastination questionnaire based on a Likert scale. The instrument validity test showed that 27 items were valid, while the reliability test obtained a Cronbach’s Alpha value of 0.803, indicating that the instrument was reliable. The results showed that self-control techniques in group counseling were effective in reducing students’ academic procrastination caused by online game addiction. This can be seen from the difference between pretest and posttest scores after treatment. Therefore, self-control techniques can be used as an alternative counseling service to help students improve self-regulation and reduce procrastination behavior.